Co-relation between depression, cognition and activities of daily livings in normal elderly people living in old age homes and communities of Kanpur, U.P. - sethi, V.; Gupta, S.; Parvez, S. (Scientific Journal of Medical Science, 2013)
Depression is less prevalent among older adults than younger adults but can have serious consequences3. Geriatric depression is associated with an increased rate of medical comorbidities, and an increase in premature death 15The need to focus on activities of daily living as a fundamental outcomes is well justified as persons who are disabled in activities of daily living function cannot successfully live alone7.Methodology: A survey was conducted by taking 200 elderly subjects including males and females. Two groups were taken having 100 subjects in each group one from OLD age homes of Kanpur and other from communities of Kanpur and Scales like MMSE, GDS and BARTHEL INDEX OF DAILY LIVINGS were used to get the scores for cognition, depression and ADL’s level and thereby a correlation was finded out among all of these variables.Results: Results of the study shows that there is a strong correlation among GDS and MMSE scores, whereas moderate correlation among Barthel index and GDS scores and mild correlation was found between Barthel index and MMSE scores which shows that depression and cognition are strongly correlated.Empirical evidence indicates that behavioral therapy, cognitive behavioral therapy, cognitive bibliotherapy, problem solving therapy, brief psychodynamic therapy, and life review/reminiscence therapy are effective but too infrequently used with older adults15.Therefore these regimes may further be added in rehab setups to cope up depression in elderly people living in community and old age homes of Kanpur